Análise da utilização da técnica do origami no design de embalagens contemporâneas - Kemura, Karen Eliane (2013)
This search shows the origami`s technique and your representation from the analysus of the contemporary packaging that have espacial formats. Counting since thet history of the paper`s discovery until the invention ad evolution of the origami and presenting an analysis of some packaging that can have this type of technique. Pointing, in the end, the advantages and disadvantages about this process.